Patients' Knowledge and Awareness towards Use of Antibiotics in Bangladesh: A Cross-sectional Study Conducted in Three Tertiary Healthcare Centers in Bangladesh - Saha, Moni Rani; Sarwar, Shammy; Shill, Manik Chandra; Shahriar, Mohammad (Stamford Journal of Pharmaceutical Sciences, 2011)
This study is aimed to estimate general knowledge and awareness of patients regarding use of antibiotics to find out possible reasons of irrational use of antibiotics in Bangladesh. It was a questionnaire based crosssectional health survey conducted on 350 subjects aged 18 or over who came to get service at three tertiary healthcare centers named Dhaka Medical College (DMC) Hospital, Sir Salimullah Medical College (SSMC) Mitford Hospital and Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital of Dhaka, Bangladesh. It was found from the study that the general knowledge of the patients about the indication of antibiotics was very poor. Majority of the patients did not know the appropriate use of antibiotics. Only 26% respondents answered correctly that antibiotics are indicated for bacterial infections. In addition, 38.97% of them also did not know that an antibiotic is a prescription drug and should not be used without doctor’s prescription. The awareness about the patients towards use of antibiotics was also poor. A very high percentage of the patients (51.71%) answered that they do not complete the full course of therapy. Surprisingly, 39.14% of the patients replied that they stop antibiotics when the symptoms disappear and remarkably 14.29% just make the dose double if they forget to take due dose. On the other hand, 28.86% of the patients said that they do not maintain dosing schedule during the course of therapy. Moreover, prevalence of self-medication with antibiotics in cold and fever was also extremely high (60.86%). This study indicates that there is an urgent need of health education for the community to increase knowledge and awareness about use of antibiotics to decrease the self-medication and inappropriate use of antibiotics. Key words: Antibiotics; General Knowledge; Awareness; Tertiary Healthcare Center; Health Education DOI: 10.3329/sjps.v3i1.6799 S. J. Pharm. Sci. 3(1): 54-58